2019
DOI: 10.3892/mmr.2019.10535
|View full text |Cite
|
Sign up to set email alerts
|

An 8‑gene signature predicts the prognosis of cervical cancer following radiotherapy

Abstract: Gene expression and DNA methylation levels affect the outcomes of patients with cancer. The present study aimed to establish a multigene risk model for predicting the outcomes of patients with cervical cancer (CerC) treated with or without radiotherapy. RNA sequencing training data with matched DNA methylation profiles were downloaded from The Cancer Genome Atlas database. Patients were divided into radiotherapy and non-radiotherapy groups according to the treatment strategy. Differently expressed and methylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Using lung cancer data from TCGA, a seven-gene model was able to predict prognosis [ 26 ]. An eight-gene prognostic model was reported to have predictive power for cervical cancer prognosis [ 19 ]. Ding et al identified a potential three-gene signature (MSRB3, CENPM, ZIC2) that can predict the prognosis of cervical cancer through the TCGA dataset, which is expected to provide a basis for the prognostic evaluation of patients in the future [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using lung cancer data from TCGA, a seven-gene model was able to predict prognosis [ 26 ]. An eight-gene prognostic model was reported to have predictive power for cervical cancer prognosis [ 19 ]. Ding et al identified a potential three-gene signature (MSRB3, CENPM, ZIC2) that can predict the prognosis of cervical cancer through the TCGA dataset, which is expected to provide a basis for the prognostic evaluation of patients in the future [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that a 70-gene signature can be used as a predictor of the therapeutic effect of individualized systemic treatment of advanced-stage cervical cancer, which can help prolong the survival time of patients [ 18 ]. Xie et al found that an 8-gene signature can predict the prognosis of patients with cervical cancer after radiotherapy [ 19 ]. Cai et al reported that a glycolysis-related six-gene signature can be used as a prognostic marker to accurately predict the prognosis of cervical cancer patients [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, parallel assessment and blindness are necessary during measurement procedures to ensure quality. Additionally, despite the increasing number of research on the predictive value of omics (35)(36)(37), the inclusion of omics into a conventional prediction model needs to be discussed considering the accessibility of these predictors and cost-effectiveness issues, especially in countries with middle or low income. Besides this, treatment is very important for the prognosis of cervical cancer patients, and different surgical methods may lead to different survival outcomes (38), but treatments were considered a predictor only in 18 models, which indicates that prognostic models tailored to different treatment modalities are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Three CSCC prognostic models (namely, the 8-, 5-and 3-gene signature) (36)(37)(38) reported in literature were selected, which were then compared with the 8-stemness gene signature constructed in our study. The corresponding Riskscore values of each prognostic model were calculated based on gene expression pro les for samples derived from TCGA-CSCC dataset, which were further converted to zscore values.…”
Section: Comparison Between Our 8-stemness Gene Signature Risk Model mentioning
confidence: 99%